ANALYSIS OF VILLAGE GOVERNMENT BUREAUCRACY PERFORMANCE OF VILLAGE OFFICIALS IN BERASTAGI DISTRICT, KARO REGENCY - Agretha, Sella (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2023)
This study aims to analyze the performance of village government bureaucracy, specifically the apparatus of Rumah Berastagi Village in Berastagi District, Karo Regency. Village bureaucratic performance is a crucial indicator of the success of effective, efficient, and accountable regional governance, particularly in the implementation of village autonomy in accordance with Law Number 6 of 2014 concerning Villages. In this study, performance is measured through several key indicators: efficiency, effectiveness, responsiveness, accountability, and the quality of public services provided by village officials to the community. The research approach used is descriptive qualitative, with data collection techniques including observation, in-depth interviews, and documentation. Informants included the village head, village officials, community leaders, and village residents as service users. The results indicate that the performance of Rumah Berastagi Village officials is generally not fully optimal. The effectiveness of public service programs still faces various obstacles.